Analysis of Nursing Care in Hypertensive Patients with Acute Pain Nursing Problems Given Dry Cupping Therapy Combined with Acupressure at Dawan Usadha Clinic - Putri, I Gusti Ayu Winda Dharmaning; Sari, Ni Luh Putu Dian Yunita; Prihandani, I GAA Sherlyna (PROMOTOR, 2025)
The risk of increased blood pressure will occur at the age of >50 years. The incidence of hypertension is increasing with the age of a person. If the blood vessels narrow, the flow of the arteries will be disrupted, where there will be a decrease in O2 (oxygen) and an increase in CO2 (carbon dioxide), resulting in pain. Non-pharmacological therapy that can reduce pain in hypertensive patients is dry cupping combined with acupressure. The implications of dry cupping therapy combined with acupressure are carried out 3 times a day in 1 week with a duration of 20 minutes. On the third day of the patient pain scale visit, the patient was measured using a numerical rating scale in the first patient on the pain scale of 3, the second patient on the pain scale of 3, and the third patient on the pain scale of 2. After being given dry cupping therapy combined with acupressure with acute pain problems, it was concluded that the pain level decreased after being given dry cupping therapy combined with acupressure.